Islamic Education Curriculum for Early Childhood in the Perspective of the Qur'an - Aziz, Mursal; Sitorus, Muhammad Walimsyah; Susilawati, Susilawati (Al-Ulum: Jurnal Pendidikan Islam, 2025)
The Islamic Education Curriculum for Early Childhood (PAUD) has an important role in shaping the character and morals of children from an early age. The perspective of the Qur'an is the main basis for designing a curriculum that can integrate Islamic teachings into children's daily lives. The Qur'an as a guide to life provides guidance related to character formation, development of spiritual intelligence, and instilling moral values that must be applied in early childhood education. In the perspective of the Qur'an, education for children is taught with a loving approach, the formation of faith, and an emphasis on noble morals. Concepts such as monotheism, kindness, honesty, and emotional management (patience, gratitude, tawakal) are values that can be used as a basis for the PAUD curriculum. This article aims to analyze how the principles contained in the Qur'an can be implemented in the Islamic Education curriculum for early childhood, so that it can facilitate the development of children's potential holistically, both in terms of spiritual, emotional, and moral aspects. It is hoped that the implementation of this curriculum will produce a generation that is not only intellectually intelligent, but also strong in religious values and good character.